2007
DOI: 10.1007/s11240-007-9202-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of somatic embryogenesis and plant regeneration in Japanese larch (Larix leptolepis)

Abstract: Different nitrogen sources, abscisic acid (ABA), gellan gum at various concentrations, and osmotica were evaluated for their effects on maturation of somatic embryo (SE) in Japanese larch (Larix leptolepis). Different concentrations of L-glutamine or casein hydrolysate (CH) in the medium were also compared. The highest number of matured embryos was obtained with ½ Litvay (LM) medium supplemented with 1.71 mM Lglutamine and 250 mg l -1 CH. In terms of osmoticum effect, the highest number of cotyledonary SEs was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 10 publications
4
25
0
3
Order By: Relevance
“…The effectiveness of organic nitrogen source like glutamine for enhanced multiplication has been reported for some other plant species also (Sanjaya et al, 2005;Vasudevan et al, 2004). It has been suggested that positive effect of organic nitrogen, in comparison to that of inorganic sources is associated to enhanced mobility of the former at a lower energy cost than the later (Kim and Moon, 2007). No report of use of amino acids in the tissue culture study of Kinnow, in particular, and citrus species in general, is available, to the best of our survey.…”
Section: Discussionmentioning
confidence: 97%
“…The effectiveness of organic nitrogen source like glutamine for enhanced multiplication has been reported for some other plant species also (Sanjaya et al, 2005;Vasudevan et al, 2004). It has been suggested that positive effect of organic nitrogen, in comparison to that of inorganic sources is associated to enhanced mobility of the former at a lower energy cost than the later (Kim and Moon, 2007). No report of use of amino acids in the tissue culture study of Kinnow, in particular, and citrus species in general, is available, to the best of our survey.…”
Section: Discussionmentioning
confidence: 97%
“…Among the factors influencing the somatic embryogenesis initiation, the appropriate developmental stage of zygotic embryos seemed the most critical. The optimal developmental stage for many conifer species has been reported in terms of seed collection date or time after fertilization (Becwar et al, 1990;Tautorus et al, 1991;Lelu et al, 1994b;Jain et al, 1995;Zoglauer et al, 1995;Lelu et al, 1999;Kim et al, 1999). However, due to the difficulty in determining the precise time of fertilization in open-pollinated cones and the fact that the variation in the zygotic embryo development depends on weather and location, the criteria for explant collection for ECI cannot be easily generalized.…”
Section: Embryogenic Culture Initiation (Eci)mentioning
confidence: 99%
“…Sometimes however, the initiation of somatic embryogenesis may not result in the establishment of an embryogenic line because the ensuing ET ceases to proliferate, making it important to distinguish between the initial extrusion from an explants and continuous growth, when assessing the success rate (Klimaszewka et al, 2007). Kim et al (1999) reported that from 294 lines initiated in Larix leptolepis, only one embryogenic cell line could be proliferated. These results suggest that the capture of stable cell lines should be the optimal criterion by which to compare the ability of somatic embryogenesis initiation among species and families.…”
Section: Embryogenic Culture Initiation (Eci)mentioning
confidence: 99%
“…Larix속 수종의 체세포배 유도에 관한 연구는 Nagmani 와 Bonga (1985)가 유럽낙엽송 (L. decidua)의 배유 (female gametophyte)조직으로부터 배발생조직을 처음으로 유도한 이후로 L. laricina (Klimaszewska et al 1997), L.×leptoeuropaea (Lelu et al 1994), L. occidentalis (Thompson and von Aderkas, 1992) 등의 수종에서 이루어졌으며 낙엽송의 경우 Kim 등 (1999;2007 …”
Section: 낙엽송의 클론증식은 삽목방법이 가장 널리 이용되고 있으나 삽목에 사용되는 삽수는 모수의 연령이 높아질수 록 unclassified